(untitled) (GEOgraphia, 2010)
Este trabalho busca analisar as comunidades negras rurais do norte do Espírito Santo a partir das características e práticas camponesas na reapropriação de seu território. Estas práticas de territorialidade retomam antigas origens e saberes, e vêm sendo fortalecidaspela incorporação do direito étnico ao território, ora afirmado pelo Estado por meio de seureconhecimento como "comunidades remanescentes de quilombos". Abstract This work aims to analyse the rural black communities of north Espírito Santo state, in Brazil, from the peasants characteristics and practices in the reappropriation of their territov. These practices of territoriality retake old origins and wisdoms, and they are being stressed through the incorporation of ethnic rights to tenitory, at the same time legitimated by the State through its recognition as "communities remaining of quilombos".